The Theory of Sovering Debt and Spain under Philip II - Conklin, James (Journal of Political Economy, 1998)
This paper examines lending by a Genoese‐led cartel to philip II of Spain (1556–98) from the perspective of theory on sovereign debt. Models in this literature suggest that the Genoese linked specie deliveries from Spain to the Low Countries to lending in order to create a penalty to enforce their loans. The king tried to renege, the Genoese applied the penalty, and the king ultimately repaid: When the episode is used to examine theory, the Crown's observed debt ceiling and estimates of its cost of enduring the penalty and its ability to repay are in line with predctions of Bulow and Rogoff. The nature of the penalty has the flavor of Gole and Kehoe's model; its observation on the “path of play” is suggestive of Atkeson's model.